Development of PBL Based E-Modules to Boost Students' Science Process Skills - Azrul Hamidi; Rida Akmala; Suyanta; Insih Wilujeng (Postgraduate, University of Mataram, 2024)
This research is Research and Development (R&D) research that follows the ADDIE development model which integrates five stages including analysis, design, development, implementation and evaluation. This research aims to produce a PBL-based e-module that is able to stimulate and improve students' science process skills. This research uses a number of assessment instruments to measure the quality and effectiveness of the e-module being developed, including an e-module validation sheet, a practicality assessment sheet by the teacher, and an observation sheet on students' science process skills. These instruments help researchers gain an in-depth understanding of the extent to which the e-modules developed meet the criteria for suThis research is Research and Development (R&D) research that follows the ADDIE development model which integrates five stages including analysis, design, development, implementation and evaluation. This research aims to produce a PBL-based e-module that is able to stimulate and improve students' science process skills. This research uses a number of assessment instruments to measure the quality and effectiveness of the e-module being developed, including an e-module validation sheet, a practicality assessment sheet by the teacher, and an observation sheet on students' science process skills. These instruments help researchers gain an in-depth understanding of the extent to which the e-modules developed meet the criteria for success and relevance in improving student learning, especially students' science process skills. The e-module validation results show that the e-module is valid with a percentage of 89.02% reaching very feasible criteria. The practical results of this e-module are very practical in terms of material, appearance, language and use. The results of observations of students' science process skills when using PBL-based e-module products are also very suitable for all student groups. From these results it is concluded that the e-module can be used in the class VII science learning process regarding classification of materials and their changes.ccess and relevance in improving student learning, especially students' science process skills. The e-module validation results show that the e-module is valid with a percentage of 89.02% reaching very feasible criteria. The practical results of this e-module are very practical in terms of material, appearance, language and use. The results of observations of students' science process skills when using PBL-based e-module products are also very suitable for all student groups. From these results it is concluded that the e-module can be used in the class VII science learning process regarding classification of materials and their changes.